2016
DOI: 10.1021/acsami.6b02662
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Dendrimer-Grafted Graphene Oxide Mediated Anti-miR-21 Delivery With an Activatable Luciferase Reporter

Abstract: MicroRNAs (miRNAs) are a class of post-transcriptional gene regulators involved in various physiological processes including carcinogenesis, and they have emerged as potential targets for tumor theranostics. However, the employment of antisense oligonucleotides, termed anti-miRs, for antagonizing miRNA functions in vivo has largely been impeded by a lack of effective delivery carriers. Here, we describe the development of polyamidoamine (PAMAM) dendrimer and polyethylene glycol (PEG)-functionalized nanographen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…The miRNAs (miR15a 11 , miR155 11 and miR-21 5 ) in different tumour environments can be detected by enhanced LNA FISH probes with 11 or without 5 amplification methods. The miR22 67 from A549 cells and miR16 74 from chemoresistant SGC7901/VCR cells as well as miR16 74 from xenografts were detected by reporter gene systems (Fig. 17).…”
Section: Rna Imaging Applicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…The miRNAs (miR15a 11 , miR155 11 and miR-21 5 ) in different tumour environments can be detected by enhanced LNA FISH probes with 11 or without 5 amplification methods. The miR22 67 from A549 cells and miR16 74 from chemoresistant SGC7901/VCR cells as well as miR16 74 from xenografts were detected by reporter gene systems (Fig. 17).…”
Section: Rna Imaging Applicationsmentioning
confidence: 97%
“…Ko et al applied a CMV/Gluc/3×PT_mi124a reporter gene system 71 , illustrating the miR124a-dependent decrease of Gluc reporter activity during neuronal differentiation 70 . Wang et al developed a CMV/Fluc/3×TS_miR21 reporter system to image anti-miR21 67 . Once exogenous anti-miR-21 oligonucleotides carried by GO-PEG-dendrimer enter the cells, they inhibit the functions of miR-21, and therefore block miR-21 from binding to the 3′-UTR of luciferase, activating the luciferase reporter and inducing bioluminescence 67 .…”
Section: Probes Imaging Exogenous Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al demonstrated a novel carrier denoted as NGO-PEG-dendrimers for miRNA delivery. NGO-PEG-dendrimers/anti-miRNA-21 were fabricated by conjugating PAMAM dendrimers and PEG-functionalized nanographene oxide (NGO) to 2′-O-methyl-modified anti-miRNA-21 [95]. The intravenous injection of NGO-PEG-dendrimers/anti-miRNA-21 caused a remarkable increase in bioluminescence signals within tumor areas through a luciferase reporter [95].…”
Section: Dendrimer-based Vectorsmentioning
confidence: 99%
“…When complexed with biological molecules, dendrimers are called dendriplexes, and cationic dendrimers are a practical choice of carrier for miRNA because they can readily associate with negatively charged nucleic acids. While many dendrimer types have been explored for siRNA delivery and antagomiR delivery, little research has examined the use of dendrimers for miRNA mimic delivery. Below, we describe some of the findings in this field to date.…”
Section: Polymer Nanocarriers For Mirna Deliverymentioning
confidence: 99%